2017
DOI: 10.37828/em.2017.11.13
|View full text |Cite
|
Sign up to set email alerts
|

The Predator Becomes the Prey: The Katydid Erechthis Gundlachi Bolívar, 1888 (Orthoptera: Tettigoniidae) Feeding Upon the Cuban Lizard Anolis Homolechis (Cope, 1864) (Squamata: Dactyloidae), With Some Notes on Hispaniolan Erechthis Bolívar, 1888

Abstract: This article present the case of an adult female of the katydid Erechthis gundlachi Bolívar, 1888 (Orthoptera: Tettigoniidae: Conocephalinae: Agraeciini) eating a very young juvenile of the lizard Anolis homolechis (Cope, 1864).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, in captive conditions, Naskrecki (2000) reported that Copiphora rhinoceros feeds on small Anole lizards. Nuñez Escalante et al (2021) observed a young female Cone-headed Katydid ( Copiphora cultricornis Pictet, 1888) preying on a Slender Anole ( Anolis limifrons Cope, 1862), and Erechthis gundlachi Bolívar, 1888 (also a Tettigoniidae) was recorded preying on a very young juvenile lizard, Anolis homolechis (Cope, 1864) (Yong 2017).…”
mentioning
confidence: 99%
“…However, in captive conditions, Naskrecki (2000) reported that Copiphora rhinoceros feeds on small Anole lizards. Nuñez Escalante et al (2021) observed a young female Cone-headed Katydid ( Copiphora cultricornis Pictet, 1888) preying on a Slender Anole ( Anolis limifrons Cope, 1862), and Erechthis gundlachi Bolívar, 1888 (also a Tettigoniidae) was recorded preying on a very young juvenile lizard, Anolis homolechis (Cope, 1864) (Yong 2017).…”
mentioning
confidence: 99%
“…In addition to herbivory, some orthopteran species are considered to be predatory or, at least, opportunistic predators (O'Donnell 1993;Nickle 2002;Nickle 2007). For example, some species feed on hymenopteran eggs and larvae, small spiders, oligochaetes, aphids, other small invertebrates, and even small vertebrates (Resh and Cardé 2009;Morselli 2010;Godé et al 2015;Young 2017). However, the predatory habits of orthopterans in the Neotropical region are not well documented (O'Donnell 1993; Woodrow et al 2021).…”
mentioning
confidence: 99%